2021
DOI: 10.1161/circulationaha.120.053216
|View full text |Cite
|
Sign up to set email alerts
|

Spending on Cardiovascular Disease and Cardiovascular Risk Factors in the United States: 1996 to 2016

Abstract: Background: Spending on cardiovascular disease and cardiovascular risk factors (cardiovascular spending) accounts for a significant portion of overall US healthcare spending. Our objective was to describe US adult cardiovascular spending patterns in 2016, changes from 1996 to 2016, and factors associated with changes over time. Methods: We extracted information on adult cardiovascular spending from the Institute for Health Metrics and Evaluation's disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 46 publications
1
65
0
2
Order By: Relevance
“…Disease history, stroke 18 , and renal disease 19,20 are associated with hypertension. Given that health care spending on hypertension exceeded USD 70 billion in the United States between 1996 and 2016 21 , clinicians and researchers have great interest in proactive and preventive interventions versus reactive approaches for hypertension. In this study, we demonstrated that an alternative option for potentially improving hypertension control in adults aged ≥ 65 years is habitual nighttime hot spring bathing.…”
Section: Discussionmentioning
confidence: 99%
“…Disease history, stroke 18 , and renal disease 19,20 are associated with hypertension. Given that health care spending on hypertension exceeded USD 70 billion in the United States between 1996 and 2016 21 , clinicians and researchers have great interest in proactive and preventive interventions versus reactive approaches for hypertension. In this study, we demonstrated that an alternative option for potentially improving hypertension control in adults aged ≥ 65 years is habitual nighttime hot spring bathing.…”
Section: Discussionmentioning
confidence: 99%
“…That is 1 percent of the U.S. GDP. Spending on heart disease and stroke amounts to at least $320 billion per year (Birger et al 2021). As the leading cause of death, diseases of the circulatory system take around 700,000 lives per year.…”
Section: Questioning Cancer As a Prioritymentioning
confidence: 99%
“…Coronary artery disease (CAD), driven by the underlying pathologies of endothelial dysfunction, arterial calcification, inflammation, and atherosclerosis, is a significant risk factor for myocardial infarction and stroke. In the United States, cardiovascular disease costs >$320 billion per annum, with nearly half of the country’s adult population predicted to have cardiovascular disease by 2035 [ 1 ]. This significant health burden highlights a critical unmet need for effective pharmacotherapies to lessen the morbidity and mortality associated with CAD.…”
Section: Introductionmentioning
confidence: 99%